Recurrent Blood Pressure Rise after Treatment with Anti-vascular Endothelial Growth Factor Agents - Wyssmüller, Iris; Schaal, Karen; Wolf, Sebastian; Zinkernagel, Martin (Klinische Monatsblätter für Augenheilkunde, 2020)
Background It has previously been shown that the process of anti-vascular endothelial growth factor (VEGF) injections can lead to a significant increase of blood pressure. The aim of this study was to investigate whether this blood pressure increase was reproducible with repeated anti-VEGF injections.Patients and Methods Patients with a systolic blood pressure of ≥ 180 mmHg during previous injections who were scheduled for further injections were asked to participate in this study. Systolic as well as diastolic blood pressure was measured before, during, and after the intravitreal injection process.Results Thirty-nine patients (21 females, 18 males) with a mean age of 75 years (range 34 – 94 years) were included in this extension of the FEAR study. At first, clinical systolic blood pressure rose from an average of 157.3 ± 5.9 mmHg to 175 ± 6.7 mmHg at the time of the injection process (p < 0.01). Diastolic blood pressure rose from an average of 75.72 ± 4.2 mmHg to 84.44 ± 7.3 mmHg (p < 0.13) at the time of the injection process. Overall, the majority of the participants (56%, N = 22) had a systolic blood pressure of ≥ 180 mmHg.Conclusions Our results show that the blood pressure increase occurs persistently during the injection process in some patients. Repeated episodes of severe hypertension may predispose patients to cardiovascular events, especially those with concomitant cardiovascular risk factors.
Keywords: intravitreal injection; blood pressure rise; aflibercept